Consumer protection in India - Sundaram, Satya I. (Delhi : B.R. Pub. Corp Distributed by D.K. Publishers' Distributors, 1985)
This book not only presents the plight of consumers in India but explains what the sate, consumer councils and consumers themselves have to do to strengthen the consumer movement.
Includes bibliographical references
osa 14/05/2018
Loans
Keywords: Consumer protection; Consumer education; Consumers; Trade regulation; India